Challenges in exercising the right to appeal – the case of Slovenian administrative consultation - Kovač, Polonca (Central European Public Administration Review, 2024)
Purpose: The article aims to identify systemic challenges in Slovenian administrative practice arising from an inadequately regulated right to appeal under the General Administrative Procedure Act (GAPA). For this purpose, an analysis of Administrative Consultation (AC), a legal clinic operating since 2009, was conducted. The study includes analyses of the content, complexity, and reasoning behind the occurring dilemmas as a ground for GAPA recodification. Design/Methodology/Approach: Considering the nature of the topic in the scope of administrative law, a combined qualitative approach is applied, including normative and dogmatic methods, literature analysis, case law review, basic statistics, and axiological method. Empirical research is based on over one hundred cases with questions and answers regarding GAPA interpretation in administrative practice. Findings: Administrative appeal serves multiple functions, from protecting the rights of the parties to ensuring consistent sector-specific legislation implementation. The analysis identifies systemic issues, such as: standing to file an appeal (especially for other affected persons or authorities), grounds for appeal, competence regarding appellate decisions, determining when the first-instance body can handle an appeal and when devolution is necessary, alternative dispute resolution in appeals, deadlines for lodging and deciding on appeals, and the possibility of waiving the right to appeal. In addition, the (lack of) options for digitalised proceedings is notable. These insights serve as an empirical basis GAPA recodification. Academic Contribution to the Field: The article offers a regulatory and doctrinal analysis of the relevant legal provisions (including EU law, the Slovenian Constitution, and the GAPA) focusing on the aims, locus standi, time limits, grounds, and other elements of appeals. It also explores the key findings from Slovenian case law on administrative disputes regarding appeals, as reflected in decisions by the Supreme and Administrative Courts as well as in administrative practice. Research/Practical/Social Implications: The article provides a concise overview of the relevant literature and an analysis of the rules that underpin the implementation, evaluation, and improvement of GAPA as regards the right to appeal. Based on these insights, it proposes de lege ferenda solutions for a clearer GAPA. The findings can serve as a foundation for data-based decision-making. Originality/Value: The article brings forward the study of AC as a source for systemic overview of problems in the field. With more than a hundred cases from the past 15 years analysed, it offers an objective insight into recurring dilemmas in administrative practice. The approach to identifying key challenges is consistent through the use of established and combined social sciences research methods.
Keywords: Administrative Consultation; administrative procedural law; GAPA codification; kodifikacija ZUP; pravica do pritožbe; right to appeal; Slovenia; Slovenija; Upravna svetovalnica; upravno procesno pravo